2014
DOI: 10.1177/1758834014532510
|View full text |Cite|
|
Sign up to set email alerts
|

Novel agents in development for advanced non-small cell lung cancer

Abstract: Abstract:The identification of EGFR mutations and ALK rearrangements in nonsmall cell lung cancer (NSCLC) has led to the rapid development of targeted therapies and significant changes in the treatment paradigm. Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) and crizotinib are now standard therapies for patients with the appropriate molecular alteration. Current investigations are determining the mechanisms of resistance to targeted therapies and developing novel agents to combat res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 85 publications
0
38
0
Order By: Relevance
“…Besides monitoring of response to therapy, the molecular characterization of CTCs can provide important information on therapeutic targets or resistance mechanisms (23)(24)(25)(26)(27)(28). Thus, we evaluated whether the in vivo isolated CTCs also allow subsequent molecular characterization of genes relevant to therapy of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besides monitoring of response to therapy, the molecular characterization of CTCs can provide important information on therapeutic targets or resistance mechanisms (23)(24)(25)(26)(27)(28). Thus, we evaluated whether the in vivo isolated CTCs also allow subsequent molecular characterization of genes relevant to therapy of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the objective response rate was improved with osimertinib (71%; 95% CI, 65%-76%) compared with chemotherapy (31%; 95% CI, 24%-40%) ( [90][91][92][93][94][95][96][97][98] in patients with EGFR T790M whose disease has progressed on sensitizing EGFR TKI therapy; 13% (33/253) of patients had drug-related grade ≥3 AEs with 1 fatal event from pneumonia possibly related to treatment. 39,160,161 In patients without EGFR T790M, the response rate was 21% (13/61; 95% CI, 12-34) and the PFS was 2.8 months (95% CI, 2.1-4.3).…”
Section: Egfr Tkismentioning
confidence: 99%
“…[94][95][96][97][98][99][100][101][102][103][104] Ceritinib is an orally active TKI of ALK, which also inhibits the insulin-like growth factor 1 (IGF-1) receptor but not MET. An expanded phase I trial showed that ceritinib was very active in 122 patients with locally advanced or metastatic NSCLC who have ALK gene rearrangements.…”
Section: Alk Gene Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…No agents are approved for this cohort to the date, there is a phase II trial on Selumetinib that has shown some benefit, and phase 3 is on the way. And there are some less frequent mutations, and their practical use in treatment of lung cancer is to the date not clear [9] (Figure 1). We know we can use some of the as a target, but I believe that we'll get to know much more about these oncogenes too in the nearest future.…”
Section: Introductionmentioning
confidence: 99%